Pemanfaatan Neraca Penatagunaan Tanah Dalam Mendukung Penyusunan Sistem Informasi Ketahanan Pangan Pokok Wilayah (Studi Di Kabupaten Sleman Propinsi Daerah Istimewa Yogyakarta) - Samudra Ivan Supratikno; Armaidy Armawi; Djaka Marwasta (Jurnal Ketahanan Nasional, 2016)
ABSTRACTThe development of food security towards food self-sufficiency was geared to sustained the strength of the domestic economy. Unfortunately, the development of residential necessity was not in line with the development of agricultural allocation that should be prepared as the availability of agricultural land to met the primary needs of population.The study aimed to analyzed the balance of agricultural land use and its impact on main food security. The study also aimed to determined the level of food insecurity in supporting food security analysis in the area of Sleman. The study was located in Sleman, Yogyakarta Province. The method used descriptive analytical quantitative and overlaying method to performed spatial analysis. The findings were textual and spatial data output to saw the food security condition in the study areas.Top of FormBottom of FormIn Sleman, food security condition with highly resistant level was in the district of Cangkringan, whereas in the districts of Sleman and Moyudan had experienced in a very vulnerable level.  Based on the calculated statistical indicators; the level of access to food, land use suitability, and the availability of land used as a valid and reliability aspects of food security assessment. The data used in the analysis of food security were agriculture and non-agriculture areas to determined the index value of agricultural land for determining insecurity food. According to analysis using determinant of food insecurity index, it showed  that the condition of 15 Districts in Sleman were in the category food secure areas and 2 sub-districts namely Sleman and Depok were classified into the category of potentially food-insecure areas.ABSTRAK Pembangunan ketahanan pangan menuju kemandirian pangan diarahkan untuk menopang kekuatan ekonomi domestik. Peningkatan kebutuhan permukiman sayangnya tidak sejalan dengan perkembangan terhadap alokasi kebutuhan lahan pertanian yang seharusnya juga disiapkan sebagai ketersediaan tanah pertanian untuk memenuhi kebutuhan primer penduduknya. Tujuan penelitian ini menganalisis perimbangan (neraca) penggunaan tanah pertanian dan dampaknya terhadap ketahanan pangan pokok dan mengetahui tingkat kerawanan pangan untuk mendukung analisis ketahanan pangan pokok wilayah di wilayah Kabupaten Sleman. Lokasi penelitian di Kabupaten Sleman, Propinsi Daerah Istimewa Yogyakarta. Metode penelitian menggunakan analisis kuantiatif-deskriptif dan metode tumpang susun untuk melakukan analisis keruangannya. Penelitian ini menghasilkan output data tekstual dan spatial untuk melihat kondisi ketahanan pangan di wilayah penelitian.Kondisi ketahanan pangan di Kabupaten Sleman dengan tingkatan sangat tahan pangan berada di Kecamatan Cangkringan dan yang berada dalam kategori sangat rawan pangan di Kecamatan Sleman dan Moyudan. Berdasarkan indikator yang dihitung secara statistik; tingkat akses terhadap pangan, kesesuaian penggunaan tanah dan ketersediaan tanah valid dan reliabilitas dijadikan aspek penilaian ketahanan pangan. Data neraca yang digunakan dalam analisis ketahanan pangan adalah data kawasan budidaya pertanian dan non-pertanian untuk menentukan nilai indeks luas lahan pertanian dalam penentuan kerentanan pangan.Berdasarkan analisis dengan menggunakan indeks penentu kerawanan pangan didapatkan bahwa kondisi 15 Kecamatan di Kabupaten Sleman masuk kedalam kategori tahan pangan dan 2 Kecamatan yaitu Depok dan Sleman masuk kedalam kategori daerah berpotensi rawan pangan.